ALK Inhibitors in Patients With ALK Fusion–Positive GI Cancers: An International Data Set and a Molecular Case Series. (27th April 2022) - Ambrosini, Margherita; Del Re, Marzia; Manca, Paolo; Hendifar, Andrew; Drilon, Alexander; Harada, Guilherme; Ree, Anne Hansen; Klempner, Samuel; Mælandsmo, Gunhild Mari; Flatmark, Kjersti; Russnes, Hege G.; Cleary, James M.; et al.
Abstract : PURPOSE: In GI cancers, anaplastic lymphoma kinase ( ALK ) rearrangements are extremely less frequent than in non–small-cell lung cancer but may be important to offer personalized strategies of treatment in selected patients. Data about the activity and efficacy of ALK inhibitors (ALKi) in GI cancers are scarce. MATERIALS AND METHODS: We assembled a clinical and molecular international data set of pretreated patients with metastatic or nonresectable cancers of GI primary tumor origin with documented ALK rearrangement treated with at least one line of ALKi. Measurable disease as per RECIST 1.1 was required for response analysis. RESULTS: Primary tumor sites were distributed as follows: 5 (38%) pancreas, 3 (23%) right colon, and 1 (8%) for each one of gastric, duodenal, rectal, left colon, and biliary tract sites. Seven patients (54%) were treated with alectinib, 5 (38%) with crizotinib, and 1 (8%) with entrectinib. After disease progression, five patients (38%) received a subsequent ALKi treatment line, and at the time of data cutoff date, treatment was still ongoing in two patients. Five of 12 evaluable patients (41%) achieved a partial response to first-line ALKi, five patients (41%) had stable disease, and 2 (17%) had progressive disease. No complete responses were registered. At a median follow-up of 39.6 months (interquartile range: 19.8-59.5), the median progression-free survival was 5.0 months (95% CI, 3.68 to no response) and the median overall survival was 9.3 months (95% CI, 5.46 to no response). CONCLUSION: Treatment with ALKi provides remarkable responses and clinical benefit in pretreated patients with ALK fusion–positive GI malignancies. Despite the rarity, ALK rearrangements represent an important therapeutic target in individual pretreated patients with GI solid tumors. Further work providing prospective clinical validation of this target is needed. Abstract :